Fermentation enhancement of methanogenic archaea consortia from an Illinois basin coalbed via DOL emulsion nutrition. - Dong Xiao; Su-Ping Peng; En-Yuan Wang (PLoS ONE, 2015)
Microbially enhanced coalbed methane technology must be used to increase the methane content in mining and generate secondary biogenic gas. In this technology, the metabolic processes of methanogenic consortia are the basis for the production of biomethane from some of the organic compounds in coal. Thus, culture nutrition plays an important role in remediating the nutritional deficiency of a coal seam. To enhance the methane production rates for microorganism consortia, different types of nutrition solutions were examined in this study. Emulsion nutrition solutions containing a novel nutritional supplement, called dystrophy optional modification latex, increased the methane yield for methanogenic consortia. This new nutritional supplement can help methanogenic consortia form an enhanced anaerobic environment, optimize the microbial balance in the consortia, and improve the methane biosynthesis rate.